Implementing e-Health initiatives in Zimbabwe’s public health sector - Chilunjika, Alouis; Chilunjika, Sharon R.T.; Uwizeyimana, Dominique (Journal of Economic Development, Environment and People, 2024)
The Zimbabwean government has instigated various policies and strategies as part of e-government initiatives to provide members of the public with convenient access to health information and services. Efforts have been made to embrace ICTs in Zimbabwe’s public health sector. The performance of health institutions in Zimbabwe however continues to deteriorate at a time when the use of ICTs in health is gaining momentum in Africa. This paper therefore seeks to assess the implementation of the E-health strategy revealing the current state of e-health or digital technology systems in Zimbabwe’s public hospitals. The study adopted an exploratory research design. Participants in this study were selected using purposive sampling. Data were gathered through participant observations, in-depth interviews and documentary research. The study established that even though e-health is an indispensable tool in improving quality, timely and cost effective health care, its implementation in Zimbabwe has not been easy and it is still in its infancy stages. The study concluded that e-health is a reliable tool for promoting successful and effective public health service provision in Zimbabwe. The study therefore reflects and proposes elements necessary for the successful implementation of e-health in Zimbabwe’s public health sector.